2019
DOI: 10.1002/jctb.6168
|View full text |Cite
|
Sign up to set email alerts
|

Sericin‐coated polymeric microfiltration membrane for removal of drug‐based micropollutants

Abstract: BACKGROUND: Drug-based micropollutants present in water sources are proven to be persistent, bioactive and toxic even at low concentration for human consumption. Therefore, the complete removal of the drugs from water is crucial to avoid long-term medical complications. In the present study, a novel sericin-coated adsorptive microfiltration (MF) membrane is used for the removal of drug-based micropollutants. RESULTS:The sericin-coated membrane was tested for removal of different classes of drugs from water. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…These results suggest that hydrogen and van der Waal’s were the dominant driving forces of the adsorption process. However, the positive values of and obtained for naproxen are suggestive of an endothermic mechanism driven by hydrophobic interactions between the aromatic rings of naproxen and the silk surface [ 20 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that hydrogen and van der Waal’s were the dominant driving forces of the adsorption process. However, the positive values of and obtained for naproxen are suggestive of an endothermic mechanism driven by hydrophobic interactions between the aromatic rings of naproxen and the silk surface [ 20 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was found that blending increased the adsorption capacities five-fold [ 19 ]. Verma and Subbiah [ 20 , 21 ] explored the feasibility of incorporating silk sericin, a by-product of degumming silk cocoons, for membrane modification. The modified membrane was used for the removal of ibuprofen from aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…A prior study utilized experiments using a sericin-coated hollow fiber MF membrane to evaluate the removal efficiency of various PPCPs [45]. The membrane exhibited high removal efficiencies for ibuprofen, diclofenac, amoxicillin, and ciprofloxacin due to charge-based interactions and hydrogen bonding with functional groups on the membrane surface.…”
Section: Effect Of the Physicochemical Properties Of Cecsmentioning
confidence: 99%
“…Charge-based interactions and hydrogen bonding on membrane surfaces significantly affect the removal of various drugs, including ibuprofen, diclofenac, and antibiotics. Hydrophobic interactions play a smaller role in the adsorption of certain unionized steroid drugs [45].…”
Section: Effect Of the Physicochemical Properties Of Cecsmentioning
confidence: 99%
“…Both processes showed an improved removal of MPs and their metabolites. ,, However, ozone usage is accompanied by (toxic) byproducts needing an additional separation process, whereas long contact times for the adsorption onto activated carbon (AC) are necessary, although shorter contact times for mesoporous AC have been reported . The use of multifunctional membranes or membrane adsorbers for water purification is an emerging application overcoming limitations of existing filtration processes. Advanced materials like molecularly imprinted polymers (MIPs) and MIP membranes , were designed to specifically remove one certain substance.…”
Section: Introductionmentioning
confidence: 99%